Investigation of environmental air pollution and its change assessment in Šiauliai - Paulauskas, Leonas; Klimas, Robertas (Journal of Environmental Engineering and Landscape Management, 2005)
Air pollution is one of the main reasons of pulmonary diseases, malignant tumours, allergic and other chronic deceases. In 2003, with the help of a mobile laboratory, investigation on air pollution and its distribution in Šiauliai city environment was accomplished. Measurements were performed once a month in exploratory positions deployed at 1 km intervals one from another. Average onetime annual pollutant concentration was measured, estimating one square kilometer. Concentration of CO in Šiauliai surroundings varied from 0,5 mg/m3 to 5,8 mg/m3 or by 51 % of Šiauliai area varied from 0,8 mg/m3 to 1,4 mg/m3. Concentration of NO2varied from 0,005 mg/m3 to 0,84 mg/m3 or by 57 % of the city area it varied from 0,010 mg/m3 to 0,020 mg/m3. Concentration of NO varied from 0,003 mg/m3 to 0,495 mg/m3. Concentration of SO2 varied from 0,0015 mg/m3 to 0,012 mg/m3. Concentration of O3 varied from 0,022 mg/m3 to 0,134 mg/m3. The total concentration of hydrocarbons varied from 1,5 ppm to 3,5 ppm. The highest level of pollution was observed in the central part of the city.Aplinkos oro lygio Šiauliuose tyrimai ir jo kaitos įvertinimasSantrauka. Aplinkos oro užterštumas yra viena iš pagrindinių plaučių ligų, piktybinių navikų, alerginių ir kitų lėtinių ligų priežasčių. Mobiliojoje laboratorijoje atlikti aplinkos oro užterštumo Šiauliuose 2003 metais tyrimai, analizuota teršalų pasiskirstymas miesto aplinkos ore. Matavimai buvo atliekami kartą per mėnesį tyrimo postuose, išdėstytuose 1 km atstumu vienas nuo kito. Nustatyta tokia vienkartinė vidutinė metinė teršalų koncentracija (viename kvadratiniame kilometre). CO koncentracija miesto aplinkos ore kito nuo 0,5 mg/m3 iki 5,8 mg/m3, o 51% miesto teritorijos – nuo 0,8 mg/m3 iki 1,4 mg/m3. NO2 koncentracija kito nuo 0,005 mg/m3 iki 0,084 mg/m3, o 57% miesto teritorijos – nuo 0,010 mg/m3 iki 0,020 mg/m3. NO koncentracija kito nuo 0,003 mg/m3 iki 0,495 mg/m3. SO2 – nuo 0,0015 mg/m3 iki 0,012 mg/m3. O3 koncentracija kito nuo 0,022 mg/m3 iki 0,134 mg/m3. Suminių angliavandenilių koncentracija kito nuo 1,5 ppm iki 3,5 ppm. Didžiausia teršalų koncentracija nustatyta centrinėje miesto dalyje.Reikšminiai žodžiai: aplinkos oro tarša, didžiausioji leistinoji teršalų koncentracija (DLK), mobilioji laboratorija, anglies monoksidas (CO), azoto oksidai (NO, NO2), ozonas (O3) sieros dioksidas (SO2), matavimo intervalas, teršalų koncentracija.First Published Online: 14 Oct 2010